2022
DOI: 10.1097/md.0000000000029490
|View full text |Cite
|
Sign up to set email alerts
|

Study on the mechanism of Gualou Xiebai Guizhi decoction (GLXBGZD) in the treatment of coronary heart disease based on network pharmacology

Abstract: Background: This study aims to analyze the mechanism of Gualou Xiebai Guizhi decoction (GLXBGZD) in treating coronary heart disease (CHD) utilizing network pharmacology. Methods: The GLXBGZD effective components were searched on the pharmacological database platform of the Traditional Chinese Medicine Systems Pharmacol, and its potential target was predicted. The Online Mendelian Inheritance obtained CHD disease target in Man and GeneCards database. The Venn map of the intersection target for GLXBGZD and CHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Gualou Xiebai Banxia Decoction can effectively improve the patients' TCM syndrome evaluation and vascular endothelial function, and reduce the use of nitroglycerin and its related adverse reactions. It provides a new idea and method [23] for the treatment of coronary atherosclerotic heart disease. Jiang Zhengqiang found that in the treatment process, if the use of Gualouxiebai Banxia decoction, it can effectively inhibit the inflammatory response, so as to significantly improve the therapeutic effect.…”
Section: Clinical Application Experience Summarymentioning
confidence: 99%
“…Gualou Xiebai Banxia Decoction can effectively improve the patients' TCM syndrome evaluation and vascular endothelial function, and reduce the use of nitroglycerin and its related adverse reactions. It provides a new idea and method [23] for the treatment of coronary atherosclerotic heart disease. Jiang Zhengqiang found that in the treatment process, if the use of Gualouxiebai Banxia decoction, it can effectively inhibit the inflammatory response, so as to significantly improve the therapeutic effect.…”
Section: Clinical Application Experience Summarymentioning
confidence: 99%
“…The Gualou Xiebai Guizhi decoction (GLXBGZD) is a traditional Chinese herbal formula composed of Gualou (Trichosanthis Fructus), Xiebai (Allii Macrostemonis Bulbus), Guizhi (Cmnamomi Mmulus), Zhishi (Fructus aurantii immaturus), Houpo (Magnoliae Officmalis Cortex), Fuling (Poria), Baizhu (Macrocephalae Rhizoma), Honghua (Carthami Flos), Banxia (Pinelliae Rhizoma), Chuanxiong (Chuanxiong Rhizoma), Yanhusuo (Corydalis Rhizoma), Yujin (Curcumae Radix), Gancao (Radix Rhizoma Glycyrrhizae), and other traditional Chinese medicines. GLXBGZD has the effects of warming yang and invigorating qi, eliminating phlegm and blood stasis, dredging yang, and resolving stagnation; its effectiveness in the treatment of CHD has been demonstrated in modern pharmacological studies [8][9][10].…”
Section: Introductionmentioning
confidence: 99%